Not Seeing Like a State: Mandated Reporting, State-Adjacent Actors and the Production of Illegible Subjects. (1st February 2021) - Greenberg, Max A
Abstract: Previous scholarship has described how the state "sees" subjects and is itself seen, but has not adequately considered the unfolding interactional dynamics through which subjects become legible or not. This article devises an analytical approach to the micro-dynamics of legibility. Drawing on ethnographic and interview data from violence prevention programs in Los Angeles high schools, the author examines the street-level enactment of third-party mandated reporting, which tasks state-adjacent actors with reporting when a student discloses harm. While the delegation of reporting broadens the state's horizon of visibility, it also disrupts taken for granted mechanisms of state legibility and perception. This study maps a sequence of micro-level dynamics through which illegible subjects are produced. First, third-party mandated reporters distanced themselves from the visible marks of the state in interactions with young people and presented themselves using markers of interpersonal connection. Second, students applied pre-existing situational definitions of interactions with non-state adults, opening up space for accounts of harm to emerge. Finally, facilitators produced illegibility as they discouraged young people from engagement with the state and trained them in interactional strategies of vagueness and de-personalization to make their harm illegible to policy mechanisms.